The associations of cerebrospinal fluid biomarkers with cognition, and rapid eye movement sleep behavior disorder in early Parkinson’s disease - Tao, Mingzhu; Dou, Kaixin; Xie, Yijie; Hou, Binghui; Xie, Anmu (Frontiers in Neuroscience, 2022)
Background: In Parkinson's disease (PD), levels of cerebrospinal fluid (CSF) biomarkers and progression of non-motor symptoms are associated, but the specifics are not yet clear. Objective: To investigate the associations of non-motor symptoms with CSF biomarkers in PD. Methods: We assessed 487 individuals from the Parkinson’s Progression Markers Initiative (PPMI), consisting of 155 healthy controls (HCs), and 332 PD individuals. Parkinson's patients were grouped according to non-motor symptoms and compared CSF α-synuclein (α-syn), amyloid-beta 1-42 (Aβ1-42), and total tau (t-tau) levels. Multiple linear regressions were used in baseline analysis and linear mixed-effects models in longitudinal analysis. Analyzes of mediating effects between cognition and CSF biomarkers were also performed. Results: At baseline, PD patients with cognitive impairment (PDCI) exhibited significantly lower CSF α-syn (β = -0.1244; P = 0.0469), Aβ (β = -0.1302; P = 0.0447), and t-tau (β = -0.1260; P = 0.0131) levels than those without impairments (PDCU). Moreover, a faster decline of α-syn (β = -0.2152; P = 0.0374) and Aβ (β = -0.3114; P = 0.0023) and a faster rise of t-tau (β = -0.1534; P = 0.0274) have been found in longitudinal analysis. The Aβ positive group showed an earlier decline in cognitive performance (β = -0.5341; P = 0.0180) compared to the negative Aβ group in both analyses. In addition, we found that PD patients with probable rapid eye movement sleep behavior disorder (pRBD) showed decreased CSF α-syn (β = -0.1343; P = 0.0033) levels. Finally, mediation analysis demonstrated that olfactory function partially mediated the relationship between cognition and CSF biomarkers levels. Conclusions: Our study shows that CSF biomarkers are associated with cognition at baseline and longitudinally. Cognitive impairment is more severe in patients with a heavier Aβ burden. CSF α-syn decreased in PD patients with probable rapid eye movement sleep behavior disorder. This study suggests that early recognition of increased risk of non-motor symptoms is important for disease surveillance and may be associated with pathological progression of cerebrospinal fluid markers.